Embryonic temperature influences the mucosal responses of Atlantic salmon alevins to a bacterial challenge - Malik, Muhammad Salman; Rebl, Alexander; Burgerhout, Erik; Lazado, Carlo C. (2024)
The present work investigated the effects of embryonic temperature on the responses of Atlantic salmon (Salmo salar) alevins to a bacterial challenge using Yersinia ruckeri as a model pathogen. Embryos were reared at 4°C, 6°C, and 8°C from fertilization to the eyed-egg stage. Alevins, before the start of feeding, were challenged with the pathogen, and mortality and early immune responses in mucosal organs were assessed. Fish from the 4°C and 6°C groups exhibited higher survival probabilities than those from the 8°C group 72 h post-infection. Mild histopathological changes were observed in the gills and skin across all temperature groups, with bacterial antigen detected in the secondary lamellae of gills and in the skin epithelial and basal layers. Gene expression profiling revealed slightly distinct immune gene expression patterns in low-temperature groups (4°C and 6°C) compared to the 8°C group. Gelsolin (gsn) expression increased in the skin across all temperature groups at 72 h post-infection. Claudin (cldn4) and collagen (col1a) were only upregulated in the skin of the 4°C group, while heat shock protein 70 (hspa1a) was downregulated in the gills of infected fish at 72 h compared to controls. Toll-like receptor 13 (tlr13) expression increased in infected fish at 24 h compared to controls. In the 6°C and 8°C groups, gsn expression also increased at 72 h post-infection. Cldn4 expression increased only in the gills of 8°C infected fish. This study revealed that low embryonic temperature could influence survival and mucosal immune defences following a bacterial challenge in Atlantic salmon alevins. Embryonic temperature influences the mucosal responses of Atlantic salmon alevins to a bacterial challenge acceptedVersion